Association of Hypercalcemia Before Treatment With Hypocalcemia After Treatment in Dogs With Primary Hyperparathyroidism. (18th February 2017) - Dear, J.D.; Kass, P.H.; Della Maggiore, A.M.; Feldman, E.C.
Abstract : Background: Development of hypocalcemia after treatment of hyperparathyroidism results in increased costs and risk of poorer outcomes. Previous studies have shown conflicting data about predictors of hypocalcemia after these procedures. Hypothesis/Objectives: The objective of this study was to investigate whether ionized calcium (iCa) concentrations before treatment are predictive of hypocalcemia or its clinical signs after surgical removal or heat ablation in dogs with primary hyperparathyroidism. Animals: Fifty‐four dogs with primary hyperparathyroidism (29 female, 25 male; 49 retrospective, 5 prospective). Methods: Dogs were enrolled if they met the inclusion criteria: persistent hypercalcemia (iCa >1.41 mmol/L) due to primary hyperparathyroidism and absence of preemptive calcitriol treatment. All dogs were treated with parathyroidectomy (n = 37) or percutaneous ultrasound‐guided heat ablation (n = 17). After treatment, iCa was monitored twice daily until plateau or intervention. Results: There was a moderate correlation between before‐treatment hypercalcemia and after‐treatment hypocalcemia. The prospective study was terminated due to ethical concerns given findings in the retrospective section. All dogs were placed into groups according to their pretreatment iCa: 1.46–1.61 mmol/L, 1.62–1.71 mmol/L, iCa 1.72–1.81 mmol/L, or >1.81 mmol/L. After treatment, the mean lowest iCa for each group, respectively, was 1.19, 1.18, 1.13, and 1.01 mmol/L. There was a significant association between higher group and proportion of dogs with iCa <1.00 mmol/L ( P = .014). Conclusions and Clinical Importance: This study demonstrates a moderate correlation between iCa concentration before treatment and hypocalcemia after treatment. Dogs with higher initial iCa concentrations should be treated to prevent rapid decline and development of clinical hypocalcemia.